Tingkat Usia dan Perkembangan Spiritualitas serta Faktor yang Melatarbelakanginya di Majelis Tamasya Rohani Riyadhul Jannah Palembang - Jalaluddin Jalaluddin (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
This paper is the result of research that reviewing the factors affecting spirituality, as well as the significance of the development of spirituality and age level. The conclusion of this paper, there is a significant relationship between the development of spirituality and age level. However, in addition to the age level still found other factors that affect the level of spiritual development. The factors are: the type of personality, childhood environment and understanding of the material. Religion conversion cannot be separated with the conditions and situations experienced by a person included it ages. So that the age level that is sufficiently closely linked to the physical and spiritual growth of man.